PENGARUH PEMASARAN DIGITAL DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI ERA EKONOMI DIGITAL - BAMBANG SUNTOWO; JOKO MUJI SUBAGYO; NINIS UMNASTUTI (STIEKOP MALANG PRESS, 2025)
Abstract Purpose – This study aims to analyze the influence of digital marketing and service quality on consumer purchase decisions in the digital economy era, both partially and simultaneously.. Design/methodology/approach – This research employs a quantitative approach with an explanatory research method. The sample consists of 120 respondents selected through purposive sampling, with criteria including having made an online purchase and being exposed to digital marketing promotions. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression, t-test, F-test, and classical assumption tests to ensure the validity of the model. Findings – The results reveal that effective digital marketing strategies, such as engaging content, prompt interaction on social media, and well-targeted promotional activities, can encourage consumers to make purchase decisions. In addition, good service quality, including quick response, friendliness, and reliability, plays an important role in increasing consumer interest and confidence to buy. The combination of these two factors works synergistically to strengthen consumer purchase decisions in the digital economy era. Research limitations/implications – This study is limited to respondents residing in specific regions and only covers consumers who have actively shopped online within the past six months, which may limit the generalizability of the findings.. Originality/value – This study integrates the analysis of digital marketing and service quality simultaneously in predicting consumer purchase decisions in the digital economy era. It contributes to marketing literature by emphasizing that effective digital marketing strategies must be supported by excellent service quality to maximize their impact on purchase decisions